Individual, Sociodemographic, and Environmental Factors Related to Physical Activity During the Spring 2020 COVID-19 Lockdown - Teran-Escobar, Claudia; Forestier, Cyril; Ginoux, Clément; Isoard-Gautheur, Sandrine; Sarrazin, Philippe; Clavel, Anna; Chalabaev, Aïna (Frontiers in Psychology, 2021)
Background. Research has shown important between-individual variations in physical activity (PA) during the COVID-19 lockdown. Objectives. To examine the individual, sociodemographic and, environmental factors related to PA during the Spring 2020 COVID-19 lockdown in France. To explore the mediating and moderating role of intention and self-efficacy toward PA in the relationships between sociodemographic/environmental variables and PA. Design. In this cross-sectional study, participants living in France (N= 386) completed an on-line survey between March 30 and April 10 2020. Method. Minutes per week of moderate-to-vigorous PA during the lockdown, usual physical activity before the lockdown, psychological (e.g., intention, self-efficacy, autonomous and controlled motivation), sociodemographic (gender, age, number of children) and environmental (habitat surface area, type of housing) were measured in the survey. Multiple linear regressions were used to investigate the role of these predictors on PA. Intention and self-efficacy were also examined as moderators and mediators of the association between sociodemographic/environmental factors and PA. Results. Usual physical activity before the COVID-19 lockdown, intention toward PA, habitat surface area, and controlled motivation significantly predicted PA during the lockdown. No mediating effects of intention or self-efficacy were found. Intention significantly moderated the association between gender and PA, and the association between part-time work and PA. Conclusions. PA during the COVID-19 lockdown was mainly predicted by individual factors, and notably usual PA. These results highlight the important role of habits in a highly changing context.